PENGELOLAAN DAN SISTEM PENDIDIKAN ISLAM BERWAWASAN RAHMATAN LILâALAMIN: Kajian Atas Gerakan Pendidikan Fethullah Gulen Movement - Purnomo, Hadi; Umiarso, Umiarso (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
At this time Islam is connoted as a war religion that tends to be involved in war. This stigma encouraged the emergence of Islamophobia in Western countries that were actualized in the form of hostility, harassing and even attacking the Muslims. In addition there is another very strong challenge from Muslims themselves who want to drag Islam as a religion of peace into a religion of violence. The right way as a solution of these problems are through insightful education ârahmatan lil âalaminâ. Therefore, this article tries to analyze the movement of âFethullah Gulenâ in creating world peace through education that focused on aspects of management and the education system. This article found that through insightful Islamic education ârahmatan lil âalaminâ as practiced by Fathullah Gulen Movement was able to create a school that combined academic achievement (science and religious science) and formed a golden generations. They were generations who can be ideal and universal individuals, individuals who love truth, integrate spirituality and knowledge, work to give benefit to their society.ÙØ¹ØªØ¨Ø± Ø§ÙØ¥Ø³ÙØ§Ù ÙÙ ÙØ°Ø§ Ø§ÙÙÙØª ÙØ¯ÙÙ ØØ±Ø¨ ÙÙÙÙ Ø¥ÙÙ Ø§ÙØªÙØ±Ø· ÙÙ ØØ±Ø¨. ÙØªØ´Ø¬Ø¹ ÙØ°Ù Ø§ÙÙØµÙØ© Ø¹ÙÙ Ø¸ÙÙØ± Ø±ÙØ§Ø¨ Ø§ÙØ¥Ø³ÙØ§Ù ÙÙ Ø§ÙØ¯ÙÙ Ø§ÙØºØ±Ø¨ÙØ© Ø§ÙØªÙ ÙØªÙ ØªØØ¯ÙØ«ÙØ§ ÙÙ Ø£Ù Ø£Ø¹ÙØ§Ù Ø¹Ø¯Ø§Ø¦ÙØ©Ø ÙØ§ÙØ¥Ø²Ø¹Ø§Ø¬Ø ÙÙÙØ§Ø¬ÙØ© Ø§ÙÙØ³ÙÙÙÙ. Ø¨Ø§ÙØ¥Ø¶Ø§ÙØ© Ø¥ÙÙ Ø°ÙÙ Ø ÙÙØ§Ø¬Ù Ø§ÙÙØ³ÙÙÙÙ ØªØØ¯ÙØ§Øª ÙÙÙØ© ÙÙ Ø§ÙÙØ³ÙÙÙÙ Ø£ÙÙØ³ÙÙ Ø§ÙØ°ÙÙ ÙØ±ÙØ¯ÙÙ ØªØºÙÙØ± Ø§ÙØ¥Ø³ÙØ§Ù ÙØ¯ÙÙ Ø³ÙØ§Ù Ø¥ÙÙ Ø¯ÙÙ Ø§ÙØ¹ÙÙ. Ø§ÙØ·Ø±ÙÙØ© Ø§ÙØµØÙØØ© ÙØ§ÙÙÙÙÙØ© ÙØÙ ÙÙØ®Ø±ÙØ¬ ÙÙ ÙØ¨Ø¶Ø© Ø¥Ø´ÙØ§ÙÙØ© ÙÙ ÙÙ Ø®ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ ÙÙ Ø¶ÙØ¡ ÙØ¸Ø±ÙØ© Ø§ÙØ±ØÙØ© ÙÙØ¹Ø§ÙÙÙÙ. ÙØªØØ§ÙÙ ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¥ÙÙ ØªØÙÙÙ ØØ±ÙØ© ÙØªØ Ø§ÙÙÙ ÙÙÙÙ ÙÙ Ø®ÙÙ Ø§ÙØ³ÙØ§Ù Ø§ÙØ¹Ø§ÙÙÙ ÙÙ Ø®ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ. ÙØ±ÙÙØ² ÙØ°Ø§ Ø§ÙØªØÙÙÙ Ø¹ÙÙ Ø§ÙØ¬Ø§ÙØ¨ Ø§ÙØ¥Ø¯Ø§Ø±Ù ÙØ§ÙÙØ¸Ø§Ù Ø§ÙØªØ¹ÙÙÙÙ Ø§ÙØ°Ù ÙØ§ÙØª Ø¨Ù ØØ±ÙØ© ÙØªØ Ø§ÙÙÙ ÙÙÙÙ. ØªØ¬Ø¯ ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø£ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¥Ø³ÙØ§ÙÙ ÙÙ Ø¶ÙØ¡ ÙØ¸Ø±ÙØ© Ø§ÙØ±ØÙÙ ÙÙØ¹Ø§ÙÙÙÙ ÙÙØ§ ÙØ§ÙØª Ø¨Ù ØØ±ÙØ© ÙØªØ Ø§ÙÙÙ ÙÙÙÙ ÙØ§Ø¯Ø± Ø¹ÙÙ ØªØÙÙÙ ÙØ¯Ø±Ø³Ø© ØªØ¯ÙØ¬ Ø§ÙØ¥ÙØ¬Ø§Ø² Ø§ÙØ£ÙØ§Ø¯ÙÙÙ (Ø§ÙØ¹ÙÙÙ ÙØ§ÙØ¯ÙÙ) ÙØªØ´ÙÙ Ø§ÙØ¬ÙÙ Ø§ÙØ°ÙØ¨Ù. Ø¥ÙÙ Ø¬ÙÙ ÙØ±Ø¯Ù Ø¹Ø§ÙÙÙ ÙØ«Ø§ÙÙØ ÙØ±Ø¯ ÙØØ¨ Ø§ÙØÙØ ÙÙØ¬ÙØ¹ Ø¨ÙÙ Ø§ÙØ±ÙØØ§ÙÙØ© ÙØ§ÙÙØ¹Ø±ÙØ©Ø ÙÙØ¹ÙÙ ÙÙØ§ ÙÙÙ ÙØµÙØØ© Ø§ÙÙØ¬ØªÙØ¹.